Impact of CYP2D6 Functional Allelic Variations on Phenoconversion and Drug–Drug Interactions. Issue 1 (6th November 2017) - Storelli, Flavia; Matthey, Alain; Lenglet, Sébastien; Thomas, Aurélien; Desmeules, Jules; Daali, Youssef
Abstract : We investigated whether CYP2D6 extensive metabolizers carrying a nonfunctional allele are at higher risk of phenoconversion to poor metabolizers in the presence of CYP2D6 inhibitors. Seventeen homozygous carriers of two fully‐functional alleles and 17 heterozygous carriers of one fully‐functional and one nonfunctional allele participated in this trial. Dextromethorphan 5 mg and tramadol 10 mg were given at each of the three study sessions. CYP2D6 was inhibited by duloxetine 60 mg (session 2) and paroxetine 20 mg (session 3). A higher rate of phenoconversion to intermediate metabolizers with duloxetine (71% vs. 25%, P = 0.009) and to poor metabolizers with paroxetine (94% vs. 56%, P = 0.011) was observed in heterozygous than homozygous extensive metabolizers. The magnitude of drug–drug interaction between dextromethorphan and paroxetine was higher in homozygous than in heterozygous subjects (14.6 vs. 8.5, P < 0.028). Our study suggests that genetic extensive metabolizers may not represent a homogenous population and that available genetic data should be considered when addressing drug–drug interactions in clinical practice.